Solitary Metastasis of Pulmonary Adenocarcinoma in Restricted Thyroid Gland Nodule - GÜCİN, ZÜHAL; PAŞAOĞLU, Esra; GUNVER, Feray; Gucin, ZÜHAL (My University, 2018)
Metastatic tumors of thyroid are rare and constitute 1.2% of all thyroid malignancies. Metastasis to thyroid gland from head and neck region occurs usually via direct spread. Hematogenous metastases are mostly seen in kidney, breast, and lung tumors and malignant melanomas. Thyroid gland metastasis is usually seen in widespread diseases. Solitary metastasis in this gland is extremely rare. A 68-year-old male patient was admitted to the general surgery clinic with swelling in the neck. The patient had undergone right lobectomy in another hospital due to lung cancer two years ago. Ultrasonography revealed the presence of nodules in both lobes with maximum diameter of 4.5 cm in the right lobe and 2 cm in the left lobe. Bilateral total thyroidectomy was performed. Nodules with diameter of 4.5 and 3.5 cm were observed in the right lobe. In the histopathologic examination of a small nodule, adenocarcinoma infiltration which was 2 cm in diameter was observed. Tumoral infiltration was not observed in nodule capsule and thyroid capsule. Immunohistochemically, tumor was positive for carcinoembryonic antigen (CEA), weakly positive for thyroid transcription factor-1 (TTF-1), and negative for thyroglobulin, chromogranin A, and calcitonin. Slides of lobectomy material were reexamined and it was observed that the two tumors had the same properties. The case was reported as -pulmonary adenocarcinoma metastasis in thyroid.- No other metastasis was observed in the whole body scan of the patient. In conclusion, in the presence of nodule in thyroid gland, possibility of metastasis should be considered if a history of malignancy exists.